PELATIHAN KESEHATAN TENTANG PENTINGNYA AKTIVITAS FISIK DILAKUKAN OLEH REMAJA - Anggarani, Anastasia Putu Martha; Wanda Sinawang, Gabriel; Suadnyani, Ni Ketut (Universitas 'Aisyiyah Surakarta, 2025)
The importance of physical activity for health is a major concern in efforts to improve the quality of life of the community, including among adolescents. However, students' level of awareness and understanding regarding the benefits of physical activity still needs to be improved. This community service activity aims to provide health training to high school students to enhance their understanding of the importance of physical activity. The method used is health training, which includes education, interactive discussions, and pre- and post-tests to assess changes in students' knowledge levels. Evaluation results showed a significant increase in students' understanding after participating in the training, with the percentage of students possessing good knowledge about physical activity rising from 40% to 52%. This indicates that the health training had a positive impact on increasing students' awareness and understanding of the importance of physical activity. Therefore, such training can be an effective strategy to instill healthy lifestyle habits from an early age, under the supervision of the school’s adolescent health team